Testosterone in sport - Kadi, F. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Anabolic androgenic steroids have powerful effects on lean body mass, which can be associated with an enhancement of performance. Intramuscular injection of testosterone induces an increase in net protein synthesis. At the cellular level, testosterone is associated with the hypertrophy of muscle fibres. However, there is evidence suggesting a more pronounced effect on slow type I muscle fibres. Testosterone is able to stimulate the mitotic activity of muscle satellite cells. By promoting the entry of satellite cells in the cell cycle, testosterone induces the generation of new myonuclei, which supports the hypertrophy of muscle fibres. The myotrophic effects of testosterone are medicated by androgen receptors expressed both by myonuclei and satellite cells. New studies suggest the existence of an androgen receptor-independant mode of action for testosterone. A signalling cascade dependent upon Erk and mTOR is activated in response to treatment with testosterone. Currently, the question related to the durability of the myotrophic effects after stopping testosterone usage has not been settled.